Understanding the bidirectional association between obesity and risk of psychological distress and depression in young adults in the US: available evidence, knowledge gaps, and future directions - Friedman, Michael; Chang, Ryan; Amin, Zahir Malik; Rajan, Tanuja; Singh, Rahul; Yousefzai, Samuel; Shahid, Izza; Nasir, Khurram; Javed, Zulqarnain (Frontiers in Psychiatry, 2025)
While the physical health effects of obesity are well-characterized, an emerging branch of research has shown that obesity additionally plays a critical role in one’s mental health. Young adults, in a pivotal transition phase in their lives, may be particularly prone to the concurrent effects of obesity and adverse mental health outcomes. The purpose of this review is to comprehensively examine existing data regarding the connection between obesity and two widely validated measures of mental health: psychological distress and depression. The connection between mental health outcomes and obesity is mediated by a complex interplay between biological and sociocultural factors, which is explored in this review with particular focus on younger adults aged 20-39. Further, the impact of several demographic factors including race/ethnicity, gender, and immigration status are examined closely. To our knowledge, this review is one of the first efforts to integrate existing knowledge between obesity and mental health, with particular regard for young adults and the impact of other key sociodemographic characteristics. This review has important implications at the interface of two of the most pressing public health crises in the United States.